Susu Kedelai Menurunkan Resistensi Insulin pada Model Diabetes Melitus Tipe 2 - Handayani, Wiwik; Rudijanto, Ahmad; Indra, Mohammad Rasjad (Jurnal Kedokteran Brawijaya, 2009)
Type 2 Diabetes mellitus (T2DM) is characterized by hyperinsulinemia and hyperglicemia. Soy bean Milk ishigh nutrient drink, especially its protein contain. Several researches demonstrated that soy bean proteindecrease plasma insulin and blood glucose level. The aim of this study is to investigate the effect of soy beanmilk in reducing insulin resistance of rat T2DM Model. This experimental study used pre and post test controlgroup design. Male Rattus norvegicus wistar strain 8 week old were used as animal model. T2DM rats wereconstructed by giving high fat diet and continue with injection of low dose of streptozotocin. Rats were dividedinto 7 groups (1) Negative control group (2) Positive control group (T2DM rat without soy bean milk) (3) T2DMrat that treated with genistein 15 g/kgBW (4) T2DM rat that treated with soy bean milk 10 ml/kgBW/day (5)DMT2 rat that treated with soy bean milk 30 ml/kgBW/day (6) T2DM rat that treated with soy bean milk 60ml/kgBW/day and (7) T2DM rat that treated with soy bean milk 90 ml/kgBW/day.